The Effect of Concentration of Citric Acid Solution on Extraction of Pectin from Watermelon Albedo - Tika Paramitha; Tifa Paramitha (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Watermelon albedo or the white flesh of watermelon rind contains pectin with high enough content. In this study was conducted the extraction of pectin from watermelon albedo by the liquid-solid extraction method. The citric acid solution was used as a solvent with concentrations varied by 4%, 7%, and 10%. The research steps include the pretreatment of raw material, the extraction, the posttreatment of extraction, and the analysis of pectin. The pretreatment aimed to reduce water content and reduce the size of raw material. The extraction process was the main process in which pectin dissolution occurred in the citric acid solvent. Furthermore, the posttreatment of extraction aimed to obtain pectin solid with the addition of ethanol. The final step was the analysis, including pectin yield, moisture content, methoxyl content, galacturonic acid content, and pectin functional group. Based on research obtained, an increase in the concentration of citric acid increased pectin yield, methoxyl content, and galacturonic acid content. The moisture content of pectin decreased with the increasing concentration of citric acid. Pectin yield, moisture content, methoxyl content, galacturonic acid content resulted from 10% concentration of citric acid solvent are 8.356%, 19.748%, 7.029%, and 69.048%, respectively. Based on FTIR analysis, the functional groups contained in pectin are hydroxyl group, methyl group, carbonyl group, and ether group. This functional groups are main constituents of pectin structure.